Effect of Katuk leaf (Sauropus androgynus L. Merr) suplementation in the diet on reproductive function of Quail - Sri Subekti; Sri Susilogati Sumarti; Tri Budhi Murdiarti (Indonesian Center for Animal Research and Development (ICARD), 2008)
Katuk (Sauropus androgynus L Merr) is known to contain carotenoids, vitamin E, vitamin C, protein, and sterol compounds. This study was aimed to determine whether phytosterol in Sauropus androgynus (SA) leaf affected the reproductive system of female quails. One hundred and fifty female quails were raised from 2-27 weeks old and divided into three dietary treatment, with five replicates and 10 quails in each replicate. The treatment diets were: 1) control group: diet without katuk leaf meal; 2) diet with 9% SA ethanol extract (TEK); 3) Diet containing 9% SA meal (TDK). The TDK-fed quails laid their first eggs at 46 day of age, compared with the TEK (52 day) and the control groups (53 day). The highest fertility (94.55%) and hatchability (93.29%) were obtained from the TDK fed quails at the age of 23 and 24 weeks, respectively. These findings indicated that the reproductive system of female quails were improved not only by phytosterol in SA leaf, but also by the β-carotene, vitamin C, α-tocopherol in SA leaf. Key Words: Katuk Leaf, Fertility, Hatchability, Quail